(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Education in 2030 will undergo huge changes with generation Z in the classroom. The “real digital natives” will influence economic structures as well as the educational system due to their online behaviour and increased use of technology. Teachers at the tertiary level have to be prepared for this generation, especially when integrating social media in their instruction. They have to be aware of the main differences between web writing and paper writing when it comes to blogs, wikis, eportfolios and threaded discussions in online forums. As every single person constitutes a public digital identity in social media, teachers have to know online writing competencies in order to take responsibility for their own online performance and those of their students, especially within the increasing debate of fake news. The ancient principles of truth and ethics in online media are more than ever the reliable basis for collaborative work. The EU funded project within Erasmus+, “Future-proof your classroom – teaching skills 2030”, elaborates on these competencies in order to equip teachers with digital reading and writing skills in a blended-learning course. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.